Cardiovascular Disease Screening and Clinical Predictive Models in Axial Spondyloarthropathies - Dinneen, Brona (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Background: Cardiovascular disease (CVD) remains the leading cause of mortality worldwide and is particularly concerning in patients with chronic inflammatory conditions such as axial spondyloarthropathies (axSpA). Traditional cardiovascular risk models often fail to account for the increased risk posed by chronic inflammation in axSpA patients, potentially leading to underdiagnosis of cardiovascular complications. Emerging research suggests that inflammation-driven mechanisms, in addition to traditional risk factors, play a significant role in elevating cardiovascular risk. Current screening practices are insufficient in capturing the full spectrum of cardiovascular risk in axSpA patients. Aim: This study aims to assess cardiovascular risk in axSpA patients, identify gaps in current screening practices, and evaluate the utility of carotid Doppler ultrasound for detecting subclinical atherosclerosis. Additionally, the study explores the need for incorporating novel biomarkers and imaging techniques into cardiovascular risk models to improve the detection and management of CVD in this population. Methods: The study utilized data from the Ankylosing Spondylitis Registry of Ireland (ASRI) and a specialized cardiovascular screening clinic. A comprehensive review of traditional cardiovascular risk factors was conducted, alongside inflammation markers such as C-reactive protein (CRP) and disease activity scores. Imaging techniques, including coronary artery calcium (CAC) scoring, CT angiography, and carotid Doppler ultrasound, were evaluated for their efficacy in detecting subclinical atherosclerosis in axSpA patients. A pilot study assessed the impact of a specialized cardiovascular clinic on the detection of cardiovascular risk factors. Results: The ASRI data revealed significant cardiovascular comorbidities in axSpA patients, with 21.7% having hypertension, 15.8% hyperlipidaemia, and 29% classified as obese. A pilot study demonstrated that 34% of patients were newly diagnosed with cardiovascular risk factors previously undetected by routine care, highlighting significant gaps in screening. Carotid Doppler ultrasound proved effective in identifying subclinical atherosclerosis, with 85.7% of patients showing abnormal carotid intima-media thickness (CIMT). Traditional cardiovascular risk models, such as QRisk3, significantly underestimated risk in axSpA patients, as inflammation markers like CRP did not correlate with subclinical atherosclerosis, suggesting the involvement of alternative, non-inflammatory pathways. Conclusion: The study highlights the inadequacy of traditional cardiovascular risk models in detecting cardiovascular disease in axSpA patients. Carotid Doppler ultrasound emerges as a practical and effective tool for identifying subclinical atherosclerosis, offering a non-invasive and accessible method for early detection. The findings emphasize the need for integrating advanced imaging techniques, novel biomarkers, and inflammation-specific factors into cardiovascular risk models. Routine cardiovascular screening, particularly in younger axSpA patients, is crucial for improving long-term cardiovascular outcomes and reducing the burden of cardiovascular disease in this high-risk population.
APPROVED
Keywords: Axial Spondyloarthtitis; axspa; CVD; CVD screening; carotid dopplers; risk assessment; ASRI; Rheumatic disease